PERHITUNGAN SIMPANG TAK BERSINYAL PADA JALAN TRIKORA – JALAN A. YANI (LIANG ANGGANG) KILOMETER 19 BANJARBARU - Hawinuti, Riska (Lambung Mangkurat University Press, 2024)
Jalan Trikora and Jalan A.Yani (Liang Anggang), Banjarbaru as one of the alternative routes connecting the cities of Banjarbaru, Banjarmasin, and Pelaihari have a very important role to supporting transportation flow and economic activities in the surrounding area. The choice of this location for research is due to the consistent traffic congestion at the unsignalized intersection during mornings, afternoons, and evenings, despite road widening and bridge improvements in the vicinity. The aim of this article is to calculate the traffic volume and peak road capacity at the Unsignalized Intersection at Jalan Trikora - Jalan A. Yani (Liang Anggang) Kilometer 19, Banjarbaru. This research method involves surveying and direct field observation to gather input data, which are then analyzed to obtain the desired performance results. The calculations will follow the guidelines of PKJI 2014, Chapter: Intersections. Based on the calculation results, the highest traffic volume occurred on Tuesday, June 06, 2023, from 11.00 to 12.00 WITA, reaching 2.228,00 pcu/hour, with a road capacity of 3.264,03 pcu/hour, a saturation degree of 0,681, and a delay value of 11,826 seconds/pcu, resulting in a service level classification of